The immunomodulatory parasitic worm product ES-62 reduces lupus-associated accelerated atherosclerosis in a mouse model - Aprahamian, Tamar R. (Int J Parasitol, 2015)
ES-62 is an anti-inflammatory phosphorylcholine-containing glycoprotein secreted by the filarial nematode Acanthocheilonema viteae. Accelerated atherosclerosis frequently occurs in systemic lupus erythematosus (SLE), resulting in substantial cardiovascular morbidity and mortality. We examined the effects of ES-62 in the gld.apoE(−/−) mouse model of this condition. Treatment with ES-62 did not substantially modulate renal pathology but caused decreased anti-nuclear autoantibody levels. Moreover, a striking 60% reduction in aortic atherosclerotic lesions was observed, with an associated decrease in macrophages and fibrosis. We believe that these latter findings constitute the first example of a defined parasitic worm product with therapeutic potential in atherosclerosis: ES-62-based drugs may represent a novel approach to control accelerated atherosclerosis in SLE.